Determinants of full immunization coverage among children 12–23 months of age from deviant mothers/caregivers in Ethiopia: A multilevel analysis using 2016 demographic and health survey - Mihret Fetene, Samrawit; Debebe Negash, Wubshet; Shewarega, Ever Siyoum; Asmamaw, Desale Bihonegn; Belay, Daniel Gashaneh; Teklu, Rediet Eristu; Aragaw, Fantu Mamo; Alemu, Tewodros Getaneh; Eshetu, Habitu Birhan; Fentie, Elsa Awoke (Frontiers in Public Health, 2023)
Background Despite remarkable improvements in child health services utilization, childhood immunization has been poorly implemented in Ethiopia. However, evidence on the coverage of immunization among children from mothers/caregivers with no education (non-educated mothers were the most identified risk for underutilization of services) are scarce. Therefore, this study aimed to assess the determinants of full immunization coverage among children 12–23 months of age from deviant mothers/caregivers in Ethiopia. Methods We analyzed data from the 2016 Ethiopia Demographic and Health Survey (EDHS) on a sample of 1,170 children 12–23 months of age identified from deviant mothers/caregivers (mothers/caregivers with no education) through a two-stage stratified sampling. A multilevel mixed-effect binary logistic regression analysis was used to identify the individual and community level determinants of full immunization coverage among children 12–23 months of age with their deviant mothers/caregivers. In the final model, a p-value of < 0.05 and adjusted odds ratio (AOR) with 95% confidence interval (CI) were used to select statistically significant determinants of full immunization coverage. Results The overall full immunization coverage among children 12–23 months of age identified from deviant mothers/caregivers was 27.4% (95%CI: 25.0, 31.0) in Ethiopia. Deviant mothers/caregivers who are employed (AOR = 1.69, 95%CI: 1.68, 2.45), being in the rich household wealth status (AOR = 2.54, 95%CI: 1.53, 4.22), residing in city (AOR = 5.69, 95%CI: 2.39, 13.61), having one to three (AOR: 3.28, 95% CI: 2.12–5.07) and four and more ANC follow-up during the recent pregnancy (AOR: 3.91, 95% CI: 2.45, 6.24) were the determinants that increased full immunization coverage among children 12–23 months of age. Conclusions Full immunization coverage among children 12–23 months of age from non-educated mothers/caregivers was low and far behind the national target of coverage. Therefore, a system-wide intervention should be used to enhance employability, wealth status, and key maternal health services like ANC follow-up among non-educated mothers/caregivers to increase their children's full immunization coverage.